Middle eastern genetic legacy in the paternal and maternal gene pools of Chuetas - J. F. Ferragut (Nature Portfolio, 2020)
Abstract Chuetas are a group of descendants of Majorcan Crypto-Jews (Balearic Islands, Spain) who were socially stigmatized and segregated by their Majorcan neighbours until recently; generating a community that, although after the seventeenth century no longer contained Judaic religious elements, maintained strong group cohesion, Jewishness consciousness, and endogamy. Collective memory fixed 15 surnames as a most important defining element of Chueta families. Previous studies demonstrated Chuetas were a differentiated population, with a considerable proportion of their original genetic make-up. Genetic data of Y-chromosome polymorphism and mtDNA control region showed, in Chuetas’ paternal lineages, high prevalence of haplogroups J2-M172 (33%) and J1-M267 (18%). In maternal lineages, the Chuetas hallmark is the presence of a new sub-branching of the rare haplogroup R0a2m as their modal haplogroup (21%). Genetic diversity in both Y-chromosome and mtDNA indicates the Chueta community has managed to avoid the expected heterogeneity decrease in their gene pool after centuries of isolation and inbreeding. Moreover, the composition of their uniparentally transmitted lineages demonstrates a remarkable signature of Middle Eastern ancestry—despite some degree of host admixture—confirming Chuetas have retained over the centuries a considerable degree of ancestral genetic signature along with the cultural memory of their Jewish origin.